The Concurrent and Longitudinal Associations of Bullying Perpetration, Acceptance of Partner Violence, and Adolescent Dating Violence Perpetration - Vivolo-Kantor, Alana M (2017)
Adolescent dating violence (ADV) and bullying are both serious and prevalent public health concerns with overlapping risk factors and negative health consequences. Prior research has demonstrated significant associations between these two behaviors, with some identifying bullying perpetration as a precursor to ADV perpetration. However, few studies have examined how bullying influences the development of ADV. One potential influencing factor may be attitudes towards partner violence, which has been associated with both bullying and ADV perpetration. Using longitudinal data from the Centers for Disease Control and Prevention’s (CDC) cluster randomized controlled trial of Dating Matters®: Strategies to Promote Healthy Teen Relationships (Dating Matters®), this dissertation assessed both the cross-sectional and prospective relationship between bullying perpetration, acceptance of male and female partner violence, and ADV perpetration. It also tested the indirect effect of bullying perpetration and ADV perpetration via acceptance of male and female partner violence and determined if these indirect effects were moderated by sex. Self-report data from 1,361 students in 21 standard of care schools within four sites were included in analyses. Longitudinal data from four time points (Fall 2012 or T1, Spring 2013 or T2, Fall 2013 or T3, and Spring 2014 or T4) were included. Results demonstrated that across all time points bullying perpetration and ADV perpetration were significantly associated for both males and females. Prior reports of bullying, ADV perpetration, and acceptance of female partner violence were significant predictors of future reports of bullying, ADV perpetration, and acceptance of female partner violence, respectively, with some caveats across males and females. As hypothesized, T1 bullying predicted increases in T4 ADV (β=.289; SE=.106; p = .007), but only for females. On the other hand, among males, T1 bullying predicted decreases in T2 ADV (β=-.209, SE=.098, p = .032), and T2 bullying predicted decreases in T3 ADV (β=-.239, SE=.116, p = .040). Also as hypothesized, bullying predicted acceptance of male and female partner violence for females only, and acceptance of male and female partner violence significantly predicted ADV. Several significant mediational pathways were observed for males and females, yet all were counter to hypothesized indirect paths. Findings have significant implications for not only the timing of when to implement ADV prevention programming, but also for the content that should be included within adolescent dating violence programming and the individuals most at risk who should be targeted